Transformasi Kreatif Fobia Pada Karya Seni Lukis - Tryamei, Tito (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2012)
Creation of art work â€œCreative Transformation of Phobia on Painting Art Workâ€ basically is subjective realization or personal expression. Itâ€™s a very common thing, because for translate feeling and emotion to visual language supported by experience of using media and technique. Generally, phobia caused having experience of fear, shyness and fault that there are pressed into sub conscious. For me, as artist, fear can be a positive influence, it is source of imagination to create visual objects. Iâ€™m use this phenomena fot theme creation of art works, ang I hope it can be treatment or decrease my fear.Â Keywords: creative, fobia, painting